Preparation method and application of fluorescence sensor for detecting metal ions based on nano-cluster packaged by metal organic framework

By coating a metal-organic framework on flexible fibers and using polyethyleneimine to stabilize the nanoclusters, the problem of nanocluster aggregation in solution was solved, and simple and rapid metal ion detection, especially the visual distinction of Fe3+, Co2+, and Cu2+, was achieved.

CN120759107APending Publication Date: 2025-10-10WUHAN TEXTILE UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510901558.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-01
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

In the existing technology, nanoclusters easily aggregate in solution, resulting in fluorescence quenching, which limits their application. In addition, traditional detection methods are expensive or complex to operate, making it difficult to achieve simple and rapid metal ion detection.

Method used

Flexible fibers were used as substrates, polyethyleneimine (PEI) was used as stabilizer, and metal-organic frameworks were combined to encapsulate nanoclusters. Fluorescent sensors were prepared by immersion and coating methods to prevent nanocluster aggregation, and the porous structure of the metal-organic framework was used to enhance stability and fluorescence performance.

Benefits of technology

The stability and fluorescence performance of the nanoclusters are maintained under different pH and temperature conditions, the fluorescence intensity is enhanced, and it can quickly respond to changes in metal ions, making it suitable for large-scale production and visually detecting metal ions such as Fe3+, Co2+, and Cu2+.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120759107A_ABST
    Figure CN120759107A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a fluorescence sensor for detecting metal ions based on a metal organic framework packaged nano-cluster. The preparation method comprises the following steps: by taking flexible fibers as a base material, firstly coating the surface of the flexible fibers with a metal organic framework, and then soaking the flexible fibers coated with the metal organic framework in a polyethyleneimine-terminated nano-cluster solution, thereby obtaining the metal ion detection fluorescent sensor based on the nano-cluster packaged by the metal organic framework. The polyethyleneimine is utilized to improve the stability and the fluorescence property of the nano-cluster obtained by reduction, so that the fluorescence sensor can maintain the fluorescence property under different pH values and temperature conditions. The prepared fluorescence sensor can rapidly respond to existence of target ions, fluorescence signals change obviously and rapidly, toxicity is small, reproducibility is good, the lower detection limit is low, fluorescence quenching is conducted on metal ions, and sensitivity is high.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of fluorescence detection, and particularly relates to a preparation method and application of a fluorescence sensor for detecting metal ions based on metal organic framework encapsulated nanoclusters. BACKGROUND

[0002] In the prior art, atomic absorption spectrometry and inductively coupled plasma mass spectrometry are generally used to detect the content of metal ions. The measurement result of atomic absorption spectrometry is accurate and reliable, but sample preparation is troublesome, the instrument is valuable, and there are many interferences (physical, chemical, ionization, and spectral interference) in the analysis. Inductively coupled plasma mass spectrometry requires expensive equipment and skilled operators, and has a large running cost. In comparison, the fluorescence detection method has the advantages of high sensitivity, high selectivity, fast response, simple operation, and low cost, and is particularly suitable for on-site real-time monitoring and detection of trace metal ions.

[0003] Nanoclusters have become important materials in the field of fluorescence detection due to their unique fluorescence properties and good biocompatibility. For example, the raw material of copper nanoclusters (CuNCs) is easy to obtain, has low cost, and causes little environmental pollution. However, copper nanoclusters are prone to aggregation in solution, which leads to fluorescence quenching and limits their application. SUMMARY

[0004] The purpose of the present application is to provide a preparation method of a fluorescence sensor for detecting metal ions based on metal organic framework encapsulated nanoclusters, which is simple to prepare, does not require complex equipment and high temperature and high pressure test conditions, and is suitable for large-scale production.

[0005] The preparation method uses flexible fibers as a substrate and polyethyleneimine (PEI) as a stabilizer to stabilize nanoclusters and prevent them from being oxidized and aggregated. The PEI-stabilized nanoclusters are further encapsulated with metal organic frameworks to prevent aggregation and limit their application. The two solutions are sequentially soaked to uniformly cover the metal organic framework encapsulated nanoclusters on the cotton fibers, and a fluorescence sensor for detecting metal ions based on metal organic framework encapsulated nanoclusters is obtained.

[0006] Fluorescence detection can be realized by adding a metal ion solution to the fluorescence sensor to visualize the fluorescence sensing of the fluorescence sensor for detecting metal ions based on metal organic framework encapsulated nanoclusters.

[0007] To achieve the above purpose, the present application provides a preparation method of a fluorescence sensor for detecting metal ions based on metal organic framework encapsulated nanoclusters, comprising the following steps: S1, preparing a polyethyleneimine aqueous solution and adjusting it to a predetermined pH value; S2, mixing the polyethyleneimine aqueous solution and the metal salt aqueous solution in a predetermined ratio, then adding a reducing agent, stirring to obtain a precursor solution; subsequently, irradiating the precursor solution under a UV lamp to obtain a polyethyleneimine-terminated nanocluster; S3, mixing zinc salt, nickel salt, ligand in a predetermined ratio, ultrasonic dispersion, then adding a fiber substrate, taking out the fiber substrate after reaction in a reaction kettle, washing, airing to obtain a fiber substrate wrapped with a metal organic framework; S4, immersing the fiber substrate wrapped with the metal organic framework obtained in step S3 into the nanocluster solution obtained in step S2 to obtain a fiber substrate adsorbed with polyethyleneimine-terminated nanoclusters and metal organic frameworks, washing and airing the obtained fiber to obtain a nanocluster detection metal ion fluorescent sensor based on a metal organic framework encapsulation.

[0008] Further, in step S1, the pH value of the polyethyleneimine aqueous solution is adjusted to 4-6.

[0009] Further, in step S2, the time for irradiating the precursor solution under the UV lamp is 0.5-12h.

[0010] Further, in step S3, the molar ratio of the zinc salt, nickel salt and ligand is (2.5-2):(1.5-1):1.

[0011] Further, in step S3, when reacting in the reaction kettle, the reaction temperature is 130℃-180℃.

[0012] Further, the metal salt is one of copper sulfate, copper nitrate and chloroauric acid.

[0013] Further, the zinc salt is zinc nitrate or zinc chloride, and the nickel salt is nickel nitrate or nickel chloride.

[0014] Further, the ligand is one of 2-amino terephthalic acid, 2-methyl imidazole and trimesic acid; and the reducing agent is one of ascorbic acid, sodium borohydride, glutathione and L-cysteine.

[0015] To achieve the above object, the application further provides a nanocluster detection metal ion fluorescent sensor based on a metal organic framework encapsulation, which is prepared by the preparation method in any of the foregoing technical solutions; the fluorescent sensor comprises a fiber substrate and polyethyleneimine-terminated nanoclusters encapsulated in the metal organic framework and loaded on the surface of the fiber substrate.

[0016] To achieve the above object, the application further provides an application of a metal organic framework encapsulated nanocluster metal ion detection fluorescent sensor, different kinds of ion solutions are added dropwise to the surface of the metal organic framework encapsulated nanocluster metal ion detection fluorescent sensor, different fluorescence phenomena are generated to detect metal ions; the ion types are Mg 2+ , Li + , Zr 4+ , K + , Co 2+ , Ni 2+ , Cu 2+ , Fe 3+ .

[0017] The application has the following beneficial effects: 1. The application provides a preparation method of a metal organic framework encapsulated nanocluster metal ion detection fluorescent sensor, first, a flexible fiber is used as a substrate, a metal organic framework is coated on the surface of the substrate, then the fiber substrate wrapped with the metal organic framework is immersed in a polyethyleneimine-terminated nanocluster solution to obtain the metal organic framework encapsulated nanocluster metal ion detection fluorescent sensor. The application uses polyethyleneimine (PEI) to improve the stability and fluorescence performance of the reduced nanoclusters, so that the obtained fluorescent sensor can maintain its fluorescence performance under different pH values and temperature conditions. In addition, the metal organic framework has a high specific surface area and a good pore structure, and the porous structure of the metal organic framework further protects the nanoclusters, so that the nanoclusters are not easy to aggregate or degrade in a complex chemical environment, and the stability and fluorescence intensity of the nanoclusters can be further enhanced.

[0018] 2. Compared with the fluorescence of the single nanocluster, the nanoclusters encapsulated in the metal organic framework obtained by the application have stronger fluorescence, and under the encapsulation of the metal organic framework, the emission wavelength has a blue shift, thereby causing the change of the light-emitting color. The changes of the single nanoclusters to the above three kinds of metal ions (Fe 3+ , Co 2+ , Cu 2+ ) are all fluorescence weakening or quenching, and the three kinds of metal ions cannot be well distinguished and detected. The fluorescence of the single metal organic framework is blue, and the changes of the above metal ions are not obvious compared with the copper nanoclusters. The nanoclusters protected by polyethyleneimine are encapsulated in the metal organic framework, the stability of the nanoclusters is improved, the nanoclusters still have good effects in a wider pH range, the fluorescence intensity of the nanoclusters is further improved, the fluorescence changes of the three kinds of metal ions (Fe 3+ , Co 2+ , Cu 2+ ) are different, the fluorescence changes of the three kinds of metal ions can be distinguished by the naked eye, and the three kinds of metal ions can be detected visually.

[0019] 3. The application provides a preparation method of a metal ion fluorescent sensor based on metal organic framework encapsulated nanoclusters, which is prepared by soaking and coating, has a simple preparation process, does not require complex equipment and high temperature and high pressure conditions, and is suitable for large-scale production.

[0020] 4. The application realizes preparation of a simple process, weavable, non-invasive metal organic framework encapsulated nanocluster metal ion fluorescent sensor, the prepared fluorescent sensor can quickly respond to the presence of target ions, has obvious and rapid fluorescence signal change, small toxicity, good reproducibility, low detection lower limit, metal ion fluorescence quenching, and high sensitivity. BRIEF DESCRIPTION OF DRAWINGS

[0021] Figure 1 A fibril diagram of the cotton fiber in Example 1.

[0022] Figure 2 A scanning electron microscope diagram of the cotton fiber obtained by ZnNi-MOF prepared in Example 1 after being soaked in a copper nanocluster solution.

[0023] Figure 3 A scanning electron microscope diagram of the fluorescent sensor obtained in Comparative Example 3.

[0024] Figure 4 A physical diagram of the cotton fiber after being soaked for 30 min by the polyethyleneimine stabilized copper nanocluster prepared in Example 1.

[0025] Figure 5 A physical diagram of the fluorescent sensor obtained in Comparative Example 3.

[0026] Figure 6 A physical diagram of the cotton fiber after different metal ions are added to the copper nanocluster encapsulated by ZnNi-MOF prepared in Example 1.

[0027] Figure 7 A fluorescence diagram of the copper nanocluster prepared in Example 1 and Comparative Example 3. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical scheme and advantages of the application clearer, the application is described in detail below with reference to the drawings and specific examples.

[0029] In addition, it should be further noted that the terms “comprise”, “contain” or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment comprising a series of elements not only includes those elements, but also includes other elements not explicitly listed or inherent to such process, method, article or equipment.

[0030] Nanoclusters easily aggregate in solution, resulting in fluorescence quenching, which limits their application.

[0031] The present invention provides a method for preparing a fluorescence sensor for detecting metal ions based on nanoclusters encapsulated in a metal organic framework, comprising the following steps: S1, preparing a polyethyleneimine aqueous solution and adjusting it to a predetermined pH value; The pH value of the polyethyleneimine aqueous solution is adjusted to 4-6. Preferably, the pH value is 5.

[0032] S2, mixing a polyethyleneimine aqueous solution and a metal salt aqueous solution in a predetermined ratio, then adding a reducing agent and stirring to obtain a precursor solution; then, irradiating the precursor solution under ultraviolet light to obtain polyethyleneimine-terminated nanoclusters; Wherein, the metal salt is one of copper sulfate, copper nitrate and chloroauric acid.

[0033] Copper nitrate is preferred because it is readily available and low-cost. It has good solubility in water and many organic solvents, high reactivity, and rapid chemical reaction. Furthermore, it exhibits good stability in many chemical reactions, particularly those requiring high temperatures or strong acidic conditions. During the preparation of copper nanoclusters, copper nitrate is more easily reduced, yielding uniformly sized nanoclusters.

[0034] Wherein, the reducing agent is one of ascorbic acid, sodium borohydride, glutathione and L-cysteine.

[0035] Ascorbic acid is preferred. When preparing copper nanoclusters, ascorbic acid can specifically reduce copper ions without reducing other metal ions, thereby obtaining high-purity copper nanoclusters.

[0036] The precursor solution is irradiated under the ultraviolet lamp for 0.5-12 hours.

[0037] By controlling the exposure time of the nanoclusters to ultraviolet light, the reduction of copper ions by ascorbic acid is controlled, thereby controlling the loading of the nanoclusters on the fiber substrate surface. This allows the final nanoclusters to be evenly coated on the cotton fibers, increasing their fluorescence intensity. If the exposure time is too short, the reducing agent cannot be uniformly reduced in the solution, resulting in fewer copper nanoclusters and a poor fluorescence effect.

[0038] S3, mixing the zinc salt, nickel salt, and ligand in a predetermined ratio, ultrasonically dispersing the mixture, and then adding the mixture to the fiber substrate. After the mixture reacts in a reaction vessel, the fiber substrate is removed, washed, and dried to obtain a fiber substrate coated with a metal organic framework. Wherein, the zinc salt is zinc nitrate or zinc chloride, and the nickel salt is nickel nitrate or nickel chloride.

[0039] The ligand is one of 2-amino terephthalic acid, 2-methyl imidazole, and trimesic acid.

[0040] When the reaction is carried out in a reaction kettle, the reaction temperature is 130-180℃, preferably 150℃. The reaction time is 6-18h, preferably 12h.

[0041] S4, the fiber substrate wrapped with the metal organic framework obtained in step S3 is immersed in the nanocluster solution obtained in step S2 to obtain a fiber substrate adsorbed with polyethyleneimine-terminated nanoclusters and metal organic frameworks, and the obtained fiber is washed and air-dried to obtain a nanocluster detection metal ion fluorescent sensor based on metal organic framework encapsulation.

[0042] The time for each immersion of the fiber substrate wrapped with the metal organic framework in the nanocluster solution is 5-30min.

[0043] The application also provides a nanocluster detection metal ion fluorescent sensor based on metal organic framework encapsulation, which comprises a fiber substrate and polyethyleneimine-protected nanoclusters encapsulated in a metal organic framework loaded on the surface of the fiber substrate.

[0044] The application also provides an application of a nanocluster detection metal ion fluorescent sensor based on metal organic framework encapsulation. Different types of ion solutions are added to the surface of the nanocluster detection metal ion fluorescent sensor based on metal organic framework encapsulation to produce different fluorescence phenomena for metal ion detection. The ion types are Mg 2+ , Li + , Zr 4 + , K + , Co 2+ , Ni 2+ , Cu 2+ , Fe 3+ .

[0045] The ion solution is prepared by diluting magnesium chloride, zirconium chloride, potassium chloride, lithium chloride, cobalt chloride, nickel chloride, copper chloride, and iron chloride into a solution.

[0046] The preparation method of the nanocluster detection metal ion fluorescent sensor based on metal organic framework encapsulation provided by the application will be described below in combination with specific examples.

[0047] Example 1 The example provides a preparation method of a nanocluster detection metal ion fluorescent sensor based on metal organic framework encapsulation, which comprises the following steps: S1, preparation of PEI solution and copper salt: prepare 20mg / ml polyethyleneimine (PEI) solution and 10mM copper nitrate solution, respectively.

[0048] S2, Preparation of polyethyleneimine stabilized copper nanoclusters: Take 2 ml of PEI solution into a 25 mL beaker, then add 1M nitric acid to adjust the pH of the PEI solution to 5, add 10 mM copper nitrate solution under stirring, stir to make it uniform, then add 7 mg of ascorbic acid, continue stirring for 10 min, and place it under a 365 nm ultraviolet lamp for 11 h, and reduce to obtain polyethyleneimine stabilized copper nanoclusters.

[0049] S3, cleaning the surface stains of the cotton fiber substrate: sequentially place the cotton fiber into deionized water and anhydrous ethanol for ultrasonic cleaning for 15 min, and store for standby use.

[0050] Preparation of ZnNi-MOF: weigh 0.2 mmol of zinc chloride (ZnCl2), 0.1 mmol of nickel chloride, and 0.1 mmol of 2-amino terephthalic acid with an electronic balance, dissolve them in a mixed solvent of 10 ml of DMF and 5 ml of deionized water, ultrasonic treat for 30 min, and stir for 12 h to prepare a precursor solution; then, add the cotton fiber substrate to the precursor solution, set the temperature to 150°C, and react for 12 h to obtain a cotton fiber substrate wrapped with ZnNi-MOF.

[0051] S4, washing the cotton fiber substrate wrapped with ZnNi-MOF obtained in step S3: sequentially place the cotton fiber into DMF and anhydrous ethanol for washing, and naturally air dry; After washing and air drying, the cotton fiber substrate is immersed in the copper nanocluster solution obtained in step S2 twice, each time for 30 min, to obtain a cotton fiber adsorbed with copper nanocluster ZnNi-MOF, and naturally air dry to obtain a metal organic framework encapsulated nanocluster based fluorescent sensor for detecting metal ions.

[0052] S4, preparation of different metal ion solutions: first take magnesium chloride, zirconium chloride, potassium chloride, lithium chloride, cobalt chloride, nickel chloride, copper chloride, and iron chloride powder, and dissolve them in deionized water to prepare 1M solutions.

[0053] Drop the aforementioned different metal ion solutions onto the cotton fiber containing copper nanocluster ZnNi-MOF prepared in Example 1, respectively, and place for 1 min to observe the fluorescence changes.

[0054] After adding different ions, there is no obvious change in the fluorescence of other ions, among which three ions (Co 2+ , Cu 2+ , Fe 3+ ) can be observed to change the fluorescence of the cotton fiber after being added. Specifically, when Co 2+ is added, the fluorescence of the cotton fiber is weakened and the color of the cotton fiber remains unchanged, and when Cu 2+When the solution is added to the cotton fiber containing copper nanoclusters ZnNi-MOF prepared in Example 1, the fluorescence of the solution changes. 3+ The fluorescence of the solution is quenched and the cotton fiber turns yellow.

[0055] Different concentrations of Co 2+ , Cu 2+ , Fe 3+ solutions are prepared and added dropwise to the cotton fiber containing copper nanoclusters ZnNi-MOF prepared in Example 1, and the fluorescence changes are observed.

[0056] Comparative Example 1 Comparative Example 1 provides a preparation method of a fluorescence sensor for detecting metal ions based on nanoclusters encapsulated by metal organic frameworks, which is different from Example 1 in that in step S2, the precursor solution is not subjected to ultraviolet lamp irradiation, and the rest is substantially the same as Example 1, which will not be repeated here.

[0057] Comparative Example 2 Comparative Example 2 provides a preparation method of a fluorescence sensor for detecting metal ions based on nanoclusters encapsulated by metal organic frameworks, which is different from Example 1 in that polyethyleneimine is not used, and the rest is substantially the same as Example 1, which will not be repeated here.

[0058] Comparative Example 3 Comparative Example 3 provides a preparation method of a fluorescence sensor for detecting metal ions based on nanoclusters encapsulated by metal organic frameworks, which is different from Example 1 in that step S3 is not performed, and the metal organic framework is not wrapped on the surface of the fiber substrate, and the fiber substrate is directly immersed in the nanocluster solution for 30 min, and the rest is substantially the same as Example 1, which will not be repeated here.

[0059] Comparative Example 4 Comparative Example 4 provides a preparation method of a fluorescence sensor for detecting metal ions based on nanoclusters encapsulated by metal organic frameworks, which is different from Example 1 in that step S4 is not performed, i.e., the polyethyleneimine-terminated nanoclusters are not wrapped on the surface of the fiber substrate, and the rest is substantially the same as Example 1, which will not be repeated here.

[0060] Please refer to Figures 1 to 3 , as shown in Figure 1 , which is the original drawing of the cotton fiber of Example 1. As can be seen from the drawing, the surface of the cotton fiber after cleaning treatment is smooth and free of stains.

[0061] Figure 2The scanning electron microscope image of cotton fiber after being immersed in copper nanocluster solution for the ZnNi-MOF prepared in Example 1. As can be seen from the figure, the cotton fiber wrapped with copper nanocluster ZnNi-MOF, the cotton fiber from the original smooth surface to the present surface is wrapped with evenly dispersed ZnNi-MOF particles, and the gap between ZnNi-MOF is also covered with copper nanoclusters.

[0062] Figure 3 The scanning electron microscope image of the fluorescent sensor obtained for Comparative Example 3. It can be seen that the copper nanoclusters are very small in size, and form a film on the substrate. Because of its small size, it can enter the pores of the metal organic framework, thereby facilitating encapsulation in the metal organic framework.

[0063] Please refer to Figures 4 to 5 , Figure 4 The actual picture of cotton fiber with ZnNi-MOF encapsulated copper nanoclusters prepared in Example 1. As can be seen from the figure, the cotton fiber presents greenish fluorescence under the irradiation of 365 nm ultraviolet lamp. It may be because the metal organic framework is combined with the nanoclusters in Example 1, causing the wavelength to move, thereby causing the fluorescence to change.

[0064] Figure 5 The actual picture of cotton fiber after being immersed in polyethyleneimine stabilized copper nanocluster solution for 30 min in Comparative Example 3. As can be seen from the figure, the cotton fiber presents yellowish fluorescence under the irradiation of 365 nm ultraviolet lamp.

[0065] Figure 6 The actual picture of the fluorescent sensor based on metal organic framework encapsulated nanoclusters for detecting metal ions prepared in Example 1 after different types of metal ions are added. As can be seen from the figure, the fluorescence of other ions changes little, while the fluorescence changes significantly when Co 2+ , Cu 2+ , Fe 3+ is added.

[0066] Figure 7 The fluorescence diagram of copper nanoclusters prepared in Example 1 and Comparative Example 3.

[0067] It can be seen that the fluorescence intensity of the nanoclusters encapsulated by the metal organic framework is higher, and compared with the nanoclusters alone, there is a slight blue shift in the emission wavelength, resulting in the fluorescence color of the nanoclusters encapsulated by the metal organic framework changing from the yellowish green emitted by the nanoclusters alone to greenish, and the fluorescence intensity is further improved after being encapsulated in the metal organic framework.

[0068] The fluorescent sensors prepared in Example 1 and Comparative Examples 1-4 were subjected to fluorescent sensing test, and the results are shown in the following table.

[0069] Comparing Example 1 with Comparative Example 1, the polyethyleneimine-stabilized copper nanoclusters of Comparative Example 1 do not have fluorescence when irradiated by the ultraviolet lamp. The reason is that the ultraviolet lamp can make the reducing agent uniformly diffuse, and the copper ions cannot be reduced to obtain copper nanoclusters without ultraviolet irradiation.

[0070] In Comparative Example 4, the polyethyleneimine-terminated nanoclusters are not wrapped on the surface of the fiber substrate, and only the metal organic framework ZnNi-MOF is wrapped, which emits blue light. The addition of various different metal ions does not have obvious fluorescence change, and the naked eye cannot distinguish well, and the detection of various metal ions is not good.

[0071] In Example 1, the addition of copper nanoclusters competes with transition metals (such as Fe 3+ , Cu 2+ ) for binding to the surface ligand, resulting in fluorescence quenching or fluorescence change; heavy metal Co 2+ forms a coordination compound with Cu + on the surface of the nanoclusters, and the fluorescence is weakened after the addition of Co 2+ . The addition of the nanoclusters can detect the three kinds of metal ions through fluorescence change.

[0072] In Comparative Example 2, polyethyleneimine is not added, and the cotton fiber is soaked in the copper nanocluster solution for 30 min to obtain a fluorescent sensor that presents blue color. The addition of various metal ions on the surface of the cotton thread does not change the fluorescence, because the copper nanoclusters without the addition of polyethyleneimine cannot specifically bind to various ions, resulting in no change in fluorescence.

[0073] In Comparative Example 3, the polyethyleneimine-stabilized copper nanoclusters are obtained, and are not encapsulated with the metal organic framework ZnNi-MOF. Compared with the copper nanoclusters encapsulated with the metal organic framework ZnNi-MOF in Example 1, the stability and fluorescence performance of the copper nanoclusters are not good. The reason is that the pores in the structure of the metal organic framework ZnNi-MOF can appropriately disperse the copper nanoclusters wrapped therein to prevent aggregation, thereby causing fluorescence quenching and longer preservation time.

[0074] Ensure that the reagents are fresh and not damp during use. Use beakers to respectively contain the same volume of deionized water, and measure the original pH value with a pH meter. In order to configure solutions with different pH values, a small amount of nitric acid and sodium hydroxide solution is respectively added to the deionized water. If the pH value is to be reduced, a small amount of nitric acid is added, and if the pH value is to be increased, a small amount of sodium hydroxide solution is added. After each small amount is added and stirred uniformly, the pH value is measured with a pH meter until the desired pH value is obtained. A series of solutions with pH values from 4 to 10 are configured.

[0075] The cotton fiber-based fluorescent sensors prepared in Example 1 and Comparative Examples 1-4 are respectively soaked in solutions with different pH values for 10 min, and then the cotton fiber-based fluorescent sensors are taken out to observe the fluorescence change. The results are shown in the following table.

[0076] From the above table, only the cotton fiber-based fluorescent sensor prepared in Example 1 has little change in fluorescence in the pH range of 4-10.

[0077] The cotton fiber-based fluorescent sensor prepared in Comparative Examples 2-3 has a significant change in fluorescence in the pH range of 4-10. The cotton fiber-based fluorescent sensors prepared in Comparative Examples 1 and 4 still do not have fluorescence in the pH range of 4-10. The reason is that the copper nanocluster metal-organic framework ZnNi-MOF encapsulated cotton fiber has better stability, and the polyethyleneimine and metal-organic framework ZnNi-MOF protected copper nanoclusters have little change in fluorescence under acidic and alkaline conditions, and the stability is better than that of the unprotected copper nanoclusters.

[0078] Examples 2-3 and Comparative Examples 5-7 The preparation method of the metal-organic framework encapsulated nanocluster-based fluorescent sensor for detecting metal ions provided in Examples 2-3 and Comparative Examples 5-7 is different from that of Example 1 in that the pH value of the polyethyleneimine aqueous solution is different, as shown in the following table; the rest is substantially the same as that of Example 1, which is not described here.

[0079] From the above table, the pH value has a great influence on the polyethyleneimine protected copper nanoclusters. When the pH value of the polyethyleneimine aqueous solution is adjusted to 4-6, it is beneficial to the reduction synthesis of copper ions into nanoclusters, and when the pH value is 5, the fluorescence of the nanoclusters is the strongest and presents yellow-green color. After being encapsulated by the metal-organic framework, the fluorescence becomes cyan, which may be caused by a blue shift in the emission wavelength after being encapsulated by the metal-organic framework, resulting in the fluorescence changing to cyan. The metal-organic framework encapsulated nanoclusters have a response to Co 2+ , Cu 2+ , and Fe 3+ three kinds of metal ions; while the nanoclusters synthesized at pH = 4 or pH = 6 also present yellow-green fluorescence, and the fluorescence also changes to cyan after being encapsulated by the metal-organic framework, which also has a response to Co 2+ , Cu 2+ , and Fe 3+ three kinds of metal ions. When the pH value of the polyethyleneimine aqueous solution is adjusted to 4-6, the metal-organic framework encapsulated nanoclusters have a response to Co 2+ , Cu 2+ , and Fe 3+ three kinds of metal ions. However, the synthesis of copper nanoclusters is not conducive in an excessively acidic or alkaline environment. The copper nanocluster solution obtained in an excessively acidic or alkaline environment has a very deep color. When the metal-organic framework loaded cotton thread is soaked in the copper nanocluster solution, the blue light emitted by the metal-organic framework is quenched or covered and cannot be seen.

[0080] Example 4 and Comparative Examples 8-9 Example 4 and Comparative Examples 8-9 provide a preparation method of the fluorescent sensor for detecting metal ions based on the metal organic framework encapsulated nanoclusters, which is different from Example 1 in that the molar ratio of zinc salt, nickel salt and ligand is different, and specific values are shown in the following table; the rest is basically the same as Example 1, which is not described here.

[0081] It can be seen from the experiment that the molar ratio of zinc salt, nickel salt and ligand has a greater impact on the change of fluorescence. When the molar ratio of zinc salt and nickel salt is in the range of (2.5-2):(1.5-1), the metal organic framework obtained emits blue fluorescence on the substrate, but when the molar ratio of zinc salt, nickel salt and ligand is 2:1:1, the blue light is the most uniform, and the color presents greenish after soaking the nanoclusters, which is more conducive to encapsulating nanoclusters; and when the molar ratio of zinc salt and nickel salt exceeds the range of (2.5-2):(1.5-1), the synthesized metal organic framework does not emit light, and presents yellow-green color of nanoclusters itself after encapsulating nanoclusters, which is not easy to determine whether the encapsulation is successful by naked eye, and the growth on the substrate is not uniform. Therefore, the molar ratio of zinc salt, nickel salt and ligand is selected as 2:1:1 as the best molar ratio, and this molar ratio is also used in subsequent experiments to obtain better results.

[0082] Example 5-6 Example 5-6 provides a preparation method of the fluorescent sensor for detecting metal ions based on the metal organic framework encapsulated nanoclusters, which is different from Example 1 in that the type of metal salt is changed, and specific values are shown in the following table; the rest is basically the same as Example 1, which is not described here.

[0083] In summary, the preparation method of the fluorescent sensor for detecting metal ions based on the metal organic framework encapsulated nanoclusters provided by the present application uses polyethyleneimine to prepare polyethyleneimine-terminated nanoclusters, which are then encapsulated in a metal organic framework ZnNi-MOF, and the ZnNi-MOF encapsulated copper nanoclusters are uniformly coated on cotton fibers to obtain the fluorescent sensor for detecting metal ions based on the metal organic framework encapsulated nanoclusters. The preparation process of the fluorescent sensor for detecting metal ions based on the metal organic framework encapsulated nanoclusters of the present application is simple, has low toxicity, uses reagents with low environmental hazards, is low in price and easy to obtain, the obtained fluorescent sensor has fast fluorescence response to metal ions, high sensitivity, and does not need to process the measured object, and can be used for on-site detection, and has wide application prospects in many fields such as environmental monitoring, food safety and industrial production.

[0084] The above merely describes preferred embodiments of the present application, and is not used to limit the present application, any modification, equivalent replacement and improvement within the spirit and principle of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a fluorescent sensor for detecting metal ions based on metal-organic framework-encapsulated nanoclusters, characterized in that: The following steps are involved: S1, preparing a polyethyleneimine aqueous solution and adjusting it to a predetermined pH value; S2, mixing the polyethyleneimine aqueous solution and the metal salt aqueous solution in a predetermined ratio, then adding a reducing agent and stirring to obtain a precursor solution; Subsequently, the precursor solution is irradiated under ultraviolet light to obtain polyethyleneimine-terminated nanoclusters; S3, mixing the zinc salt, nickel salt, and ligand in a predetermined ratio, ultrasonically dispersing the mixture, and then adding the mixture to the fiber substrate. After the mixture reacts in a reaction vessel, the fiber substrate is removed, washed, and dried to obtain a fiber substrate coated with a metal organic framework. S4, immersing the fiber substrate wrapped with the metal organic framework obtained in step S3 into the nanocluster solution obtained in step S2 to obtain a fiber substrate adsorbed with polyethyleneimine-capped nanoclusters and metal organic frameworks, and washing and drying the obtained fibers to obtain a fluorescent sensor for detecting metal ions based on metal organic framework-encapsulated nanoclusters.

2. The method for preparing a fluorescent sensor for detecting metal ions based on metal organic framework-encapsulated nanoclusters according to claim 1, characterized in that: In step S1, the pH value of the polyethyleneimine aqueous solution is adjusted to 4-6.

3. The method for preparing a fluorescent sensor for detecting metal ions based on metal organic framework-encapsulated nanoclusters according to claim 1, characterized in that: In step S2, the precursor solution is irradiated under the ultraviolet lamp for 0.5-12 hours.

4. The method for preparing a fluorescent sensor for detecting metal ions based on metal organic framework-encapsulated nanoclusters according to claim 1, characterized in that: In step S3, the molar ratio of the zinc salt, the nickel salt, and the ligand is (2.5-2):(1.5-1):

1.

5. The method for preparing a fluorescent sensor for detecting metal ions based on metal organic framework-encapsulated nanoclusters according to claim 1, characterized in that: In step S3, during the reaction in the reactor, the reaction temperature is 130°C-180°C.

6. The method for preparing a fluorescent sensor for detecting metal ions based on metal organic framework-encapsulated nanoclusters according to claim 1, characterized in that: The metal salt is one of copper sulfate, copper nitrate and chloroauric acid.

7. The method for preparing a fluorescent sensor for detecting metal ions based on metal organic framework-encapsulated nanoclusters according to claim 1, characterized in that: The zinc salt is zinc nitrate or zinc chloride, and the nickel salt is nickel nitrate or nickel chloride.

8. The method for preparing a fluorescence sensor for detecting metal ions based on metal organic framework-encapsulated nanoclusters according to claim 1, characterized in that: The ligand is one of 2-aminoterephthalic acid, 2-methylimidazole, and trimesic acid; and the reducing agent is one of ascorbic acid, sodium borohydride, glutathione, and L-cysteine.

9. A fluorescence sensor for detecting metal ions based on metal-organic framework-encapsulated nanoclusters, characterized by: The fluorescent sensor for detecting metal ions based on nanoclusters encapsulated in metal organic frameworks Prepared according to the preparation method according to any one of claims 1 to 8; the fluorescent sensor comprises a fiber substrate and nanoclusters protected by polyethyleneimine and encapsulated in a metal-organic framework and loaded on the surface of the fiber substrate.

10. An application of a fluorescence sensor for detecting metal ions based on metal-organic framework-encapsulated nanoclusters, characterized by: The fluorescent sensor for detecting metal ions based on nanoclusters encapsulated in metal organic frameworks Prepared according to the preparation method of any one of claims 1 to 8; adding different types of ion solutions to the surface of the fluorescence sensor for detecting metal ions based on metal organic framework encapsulated nanoclusters to generate different fluorescence phenomena to detect metal ions; the ion type is Mg 2+ 、Li + 、Zr 4+ , K + 、Co 2+ 、Ni 2+ 、Cu 2+ 、Fe 3+ .